Box-shaped cloak clasps in the Late Avar Period - Ádám Máté Horváth; Bence Gulyás (Dissertationes Archaeologicae: Ex Instituto Archaeologico Universitatis de Rolando Eötvös Nominatae)
The paper focuses on Late Avar box-shaped cloak clasps. Although only thirty specimens are known from the Carpathian Basin, they are significant due to their high-quality workmanship. The type appears mainly in the northwestern part of the Avar Khaganate, along the Danube and in the northern part of the Danube–Tisza Interfluve; its spread can be linked to the main trade routes. Based on the related find assemblages, it was in fashion from the second half of the 8th century and was still in use in the first decades of the 9th century.